Concordance Between Patients' and Surgeons' Expectations of Lumbar Surgery. Issue 4 (15th February 2021) - Mancuso, Carol A.; Duculan, Roland; Cammisa, Frank P.; Sama, Andrew A.; Hughes, Alexander P.; Lebl, Darren R.; Yang, Jingyan; Ghomrawi, Hassan M.K.; Girardi, Federico P.
Abstract : Study Design: Longitudinal cohort. Objective: The aims of this study were to measure concordance between patients' and surgeons' preoperative expectations of lumbar surgery, and determine which member of the dyad more closely predicted fulfillment of expectations, defined as patient-reported status postoperatively. Summary of Background Data: Concordant patient–surgeon expectations reflect effective communication and should foster better outcomes. Methods: Preoperatively patients and surgeons completed identical surveys measuring expectations for improvement in symptoms and physical/psychosocial function. Responses ranged from "complete improvement" to "do not have this expectation"; scores for each survey ranged from 0 to 100 (greatest expectations). Concordance between pairs of patient–surgeon scores was measured with the intraclass correlation coefficient (ICC). Postoperatively, fulfillment of expectations was measured from patient-reported amount of improvement received and was calculated as the proportion of patient-reported postoperative score relative to patient-reported preoperative score, and surgeon-reported preoperative score (range 0 [no expectations fulfilled] to >1.2 [expectations surpassed]). Clinical measures included patient-reported spine-related disability. Results: For 402 patient–surgeon pairs, mean survey scores were 73 ± 19 (patients) and 57 ± 16 (surgeons); 84% of patients had higher scores than surgeons, mainly due to expecting complete improvement, whereas surgeons expected a lot/moderate/little improvement. The ICC for the entire sample was .31 (fair agreement); for subgroups, the greatest difference in ICC was for patients with more spine-related disability (ICC = .10, 95% confidence interval [CI]:0.00–0.23) versus less disability (ICC = .46, 95% CI: 0.34–0.56). 96% of patients were contacted ≥2.0 years postoperatively. Proportions of expectations fulfilled were 0.79 (0–3.00) (patients) and 1.01 (0–2.29) (surgeons). Thus patients were less likely to anticipate subsequent postoperative status (odds ratio [OR] 0.34, 95% CI 0.25–0.45) versus surgeons who were more likely to anticipate patient-reported postoperative status (OR 2.98, 95% CI: 2.22–4.00). Conclusion: Concordance between patients' and surgeons' expectations was fair; due mostly to patients expecting complete improvement whereas surgeons expected a lot/moderate/little improvement. Compared to patients' expectations, surgeons' expectations more closely coincided with patient-reported fulfillment of expectations 2 years postoperatively. Level of Evidence: 1 Abstract : Concordance between patients' and surgeons' preoperative expectations of lumbar surgery was fair with patients more likely to expect complete improvement, whereas surgeons expected a lot, moderate, or a little improvement. Compared to patients' preoperative expectations, surgeons' preoperative expectations more closely coincided with patient-reported fulfillment of expectations 2 years postoperatively.